Enhanced large magnetic entropy change and adiabatic temperature change of Ni43Mn46Sn11 alloys by a rapid solidification method. (15th July 2015) - Zhang, Yu; Zheng, Qiang; Xia, Weixing; Zhang, Jian; Du, Juan; Yan, Aru
Abstract : The effect of arc melting and melt-spinning on magnetocaloric effect related magnetic properties of Ni43 Mn46 Sn11 alloys has been contrastively studied. Different measurements based on isothermal magnetization and heat capacity were carried out. For ribbon sample, extremely high magnetic entropy change Δ S M of 41.4 J kg −1  K −1 and adiabatic temperature change Δ T ad of 3.5 K (0–5 T) were achieved, which increases by 40.3% and 16.7% compared with that of bulk sample respectively. The martensitic transition related magnetic properties have been systematically discussed.